Teaching Strategies and the Quality of Science Education for Upper Grade Elementary School Students - Atri Yuni; Elpisah Elpisah; Rego Devila; Suarlin Suarlin (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze teachers' teaching strategies in improving the quality of science learning for upper grade students (IV, V, and VI) at the SD Inpres Perumnas II Makassar. The results show that teachers implement various strategies including selecting approaches that suit students' needs, using a variety of learning methods, actively involving students in learning activities, utilizing media that support conceptual understanding, and implementing continuous evaluation to assess learning success. All of these strategies complement each other and help create more engaging, understandable, and relevant science learning for students. Research findings also revealed that the choice of teaching strategy is influenced by several important factors: student characteristics, the characteristics of the science material being taught, the availability of learning media and facilities, the learning environment, and the desired learning objectives. These five factors serve as the basis for teachers to determine the most appropriate strategy, ensuring a more effective, focused learning process that enhances students' understanding of the material. Furthermore, this study identified several challenges teachers face in implementing science teaching strategies, such as diverse student abilities, time constraints, a lack of supporting media and facilities, sub-conducive classroom conditions, and uneven student motivation. These challenges require teachers to be creative and adapt strategies to ensure learning objectives are achieved and the quality of science instruction continues to improve.